Aplikasi Event Organizer Untuk Mendukung Kegiatan Manajemen Artis Pada PT.XYZ - Bintoro Adi Guna; Alexander Setiawan; Rudy Adipranata (Jurnal Infra, 2016)
PT. XYZ is a company based in Surabaya which has a division moving in entertainment and event industry. Its business processes include recruiting and managing artists, accepting projects from clients, and financial recording. However, all mentioned business processes are still done manually and separately, which makes the company vulnerable to mistakes, human error, and losses. To minimize the mentioned risks, an application which is able to integrate and accomodate all business processes conducted by PT. XYZ is needed.In order to accomodate the business processes at PT. XYZ, the application will be able to accept project requests from clients, including creating project budgets, assigning staffs, as well as communicating between project staffs. Furthermore, the application will also be able to create auditions for recruiting artists as well as its grading and creating recruitment contract. In regards to financial activities, the application will be able to create budgets, realizing them, as well as processing all the available financial data into cash flow reports and financial statements.